2014
DOI: 10.1136/neurintsurg-2014-011325.rep
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of giant vertebrobasilar aneurysm following flow diversion: mechanical stretch as a potential mechanism for early aneurysm rupture

Abstract: A patient with a giant symptomatic vertebrobasilar aneurysm was treated by endoscopic third ventriculostomy for obstructive hydrocephalus followed by treatment of the aneurysm by flow diversion using a Pipeline Embolization Device. After an uneventful procedure and initial periprocedural period, the patient experienced an unexpected fatal subarachnoid hemorrhage 1 week later. Autopsy demonstrated extensive subarachnoid hemorrhage and aneurysm rupture (linear whole wall rupture). The patent Pipeline Embolizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…Nearly half of the previous reports have hypothesized that inflammation may be the main cause of early IA rupture. 2,4,5,8,9,13 Other putative mechanisms have implicated thrombolysis allowing for recanalization of an IA aneurysm and altered flow conditions within its lumen that may lead to its rupture. 10 Others have identified that rupture is caused by mechanical stress associated with either thrombus growth or changes in inflow and hemodynamics, reduced flow within the aneurysm, and then altering pressure in the weakened aneurysm wall.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly half of the previous reports have hypothesized that inflammation may be the main cause of early IA rupture. 2,4,5,8,9,13 Other putative mechanisms have implicated thrombolysis allowing for recanalization of an IA aneurysm and altered flow conditions within its lumen that may lead to its rupture. 10 Others have identified that rupture is caused by mechanical stress associated with either thrombus growth or changes in inflow and hemodynamics, reduced flow within the aneurysm, and then altering pressure in the weakened aneurysm wall.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of postoperative rupture of IAs following flowdiversion treatment have been explored on the basis of clinical, morphologic, clinicopathologic, and hemodynamic characteristics. 5,8,22,23 However, most studies were case reports or included many confounding factors, such as differing locations and sizes of aneurysms. In the present study, we adjusted for and matched these confounding factors with an aim of investigating the hemodynamic risk factors for postoperative rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of subarachnoid hemorrhage after flow-diverter placement has been reported as high as 4.0%. [5][6][7][8][9][22][23][24] Kulcsar et al 8 analyzed risk factors of delayed-ruptured aneurysms before and after flow-diversion treatment to understand the mechanisms leading to delayed rupture during the healing process. They proposed 4 clinical risk factors for delayed rupture: large and giant aneurysms, symptomatic aneurysms, saccular aneurysms with an aspect ratio of .1.6, and inertia-driven inflow.…”
Section: Potential Delayed Ruptured Mechanism Of Aneurysm After Flow mentioning
confidence: 99%
“…5 Early aneurysm rupture-especially large and giant aneurysms treated with flow diversion alone-is a dreaded complication. [1][2][3][4] PEDs for large or giant wide-necked intracranial aneurysms have been shown to be successful in treating wide-necked intracranial aneurysms. 2 4-6 Nevertheless, complications such as incomplete obliteration, early postoperative aneurysm rupture, thromboembolism, and intraparenchymal hemorrhage have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient the Pipeline Flex alone could have been considered, but cases of disastrous early aneurysm ruptures have been reported, especially for large and giant aneurysms treated with flow diversion alone. [1][2][3][4] We therefore used both coils and a flow diverter due to the size of the aneurysm and symptomatic presentation, which would leave the patient more vulnerable to rupture. The ability to recapture and redeploy a flow diverter was felt to be critical because it would allow precise deployment in a position to protect the origin of the PICA while building a coil mass in the aneurysm.…”
Section: Treatmentmentioning
confidence: 99%